CLUSTER CONFIGURATION FOR WASTE TREATMENT OF FOREST COMPLEX OF THE YENISEI SIBERIA - Prokhorov, Viktor; Melnikova, Elena; Zelenskaya, Tatiana; Patrina, Marina; Bezrukikh, Yuliya (Revista Inclusiones, 2020)
Subject of research: the processes of cluster generation for the waste treatment of forest complex in the macro-region of the Yenisei Siberia based on the concept of smart specialization. Object: development of a cluster configuration model for the processing of forest complex waste on the methodological basis of a system and evolutionary approach, the concept of controlled diversification of the cluster structure using related industries technologies. Methods: process audit, expert assessment, surveys, ananlysis and synthesis, time series analysis, evolutionary analysis, rank method. Results: the prospects of a combination of evolutionary and controlled processes in the cluster are assessed, possible risks of cluster development and promising technological chains for the production of high value-added end products from forest waste are identified, a target model for the configuration of a forest waste processing cluster is developed. Conclusions: the clustering of modern industries around the idea of deep processing of forest raw materials will make it possible to give the development of the region’s timber complex an appropriate degree of sustainability and innovation, avoid blocking the development of technologies, and coordinate the interests of quadhelix actors.